Falling in like - Morgan, Melissa J. (New York : Grosset & Dunlap, 2006)
The girls from Camp Lakeview keep in touch through a blog as Priya deals with a science fair project, Alyssa fights for the chance to be featured in an arts magazine, Val vies for a spot in a dance recital, and a Tori attracts the attention of the son of one of her father$1 (Bs clients.s
Keywords: Friendship -- Fiction; Blogs -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Contests -- Fiction